2020
DOI: 10.1088/1757-899x/747/1/012067
|View full text |Cite
|
Sign up to set email alerts
|

A method for cantilever dental bridge material selection based upon mastication loads: finite element analysis

Abstract: A method for cantilever dental bridge material selection based on mastication loads is proposed in the paper. The personalized cantilever dental bridge model was developed. Equivalent von Mises stresses investigated numerically in case of solid food segments mastication that concentrated in pontic and cantilever teeth fissures. It was shown that penetration of solid food (carrot, nut, biscuit) into cantilever tooth fissure may cause values of stresses higher than critical stresses of dental materials used. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…When several teeth are missing or bone is defective, the option is not necessarily dental implants, it could be cantilever dental bridge. [9] Kharakh et al at 2020 [2] concluded from their study that it is problematic and complicated to select the proper material for the prosthetic restoration because strength values should exceed 950MPa to withstand stresses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When several teeth are missing or bone is defective, the option is not necessarily dental implants, it could be cantilever dental bridge. [9] Kharakh et al at 2020 [2] concluded from their study that it is problematic and complicated to select the proper material for the prosthetic restoration because strength values should exceed 950MPa to withstand stresses.…”
Section: Discussionmentioning
confidence: 99%
“…However, to ensure success and longevity of these designs the appropriate dental material should be carefully selected. [2] Several materials have appeared in dental applications for fabrication of xed restorations. One of these materials is polyether ether ketone (PEEK).…”
Section: Introductionmentioning
confidence: 99%
“…When several teeth are missing or bone is deficient, the option is not necessarily dental implants, it could be cantilever dental bridge (Yaagoubi et al 2021). Kharakh et al (2020) concluded from their study that it is problematic and complicated to select the proper material for the prosthetic restoration because strength values should exceed 950 MPa to withstand stresses.…”
Section: Discussionmentioning
confidence: 99%
“…To summarize a better smile could be built using dental cantilever bridges. However, to ensure success and longevity of these designs the appropriate dental material should be carefully selected (Kharakh et al 2020).…”
Section: Introductionmentioning
confidence: 99%